Necrotrophic Growth of Legionella pneumophila - Temmerman, R. (American Society for Microbiology, 2006)
This study examined whether Legionella pneumophila is able to thrive on heat-killed microbial cells (necrotrophy) present in biofilms or heat-treated water systems. Quantification by means of plate counting, real-time PCR, and flow cytometry demonstrated necrotrophic growth of L. pneumophila in water after 96 h, when at least 100 dead cells are available to one L. pneumophila cell. Compared to the starting concentration of L. pneumophila, the maximum observed necrotrophic growth was 1.89 log units for real-time PCR and 1.49 log units for plate counting. The average growth was 1.57 ± 0.32 log units (n = 5) for real-time PCR and 1.14 ± 0.35 log units (n = 5) for plate counting. Viability staining and flow cytometry showed that the fraction of living cells in the L. pneumophila population rose from the initial 54% to 82% after 96 h. Growth was measured on heat-killed Pseudomonas putida, Escherichia coli, Acanthamoeba castellanii, Saccharomyces boulardii, and a biofilm sample. Gram-positive organisms did not result in significant growth of L. pneumophila, probably due to their robust cell wall structure. Although necrotrophy showed lower growth yields compared to replication within protozoan hosts, these findings indicate that it may be of major importance in the environmental persistence of L. pneumophila. Techniques aimed at the elimination of protozoa or biofilm from water systems will not necessarily result in a subsequent removal of L. pneumophila unless the formation of dead microbial cells is minimized.